(untitled) (Current Horticulture, 2024)
An experiment was conducted to study the response of subtropical ornamental tree species to five salinity levels, 0, 3, 4, 5 and 6 dS/m. Salinity effect was evaluated on the basis of changes in biomass under different salinity treatments. Different concentrations of NaCl were applied from May 2015 to October 2015 and different parameters were recorded at the end of October 2015. Aggravated salinity stress caused significant (P<0.05) reduction in all the quantified parameters. The highest salinity showed more detrimental effect compared to the control as well as lower salinity levels. At low level of salinity (0, 3, 4 dS/m), root fresh, dry weight and root length of Callistemon lanceolatus and Acacia auriculiformis slightly increased as compared to the control, whereas in Koelreutaria paniculata and Putranjiva roxburghit, biomass and root length decreased as salt concentration increased. Fresh and dry weight of stem and leaves increased as salt concentration increased in Callistemon lanceolatus and Acacia auriculiformis, whereas in Koelreutaria paniculata and Putranjiva roxburghit, it decreased.